2014
DOI: 10.1590/s1517-83822014005000031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of virulence factors among food and clinical Enterococcus faecalis strains in South Brazil

Abstract: The present report aimed to perform a molecular epidemiological survey by investigating the presence of virulence factors in E. faecalis isolated from different human clinical (n = 57) and food samples (n = 55) in Porto Alegre, Brazil, collected from 2006 to 2009. In addition, the ability to form biofilm in vitro on polystyrene and the β-haemolytic and gelatinase activities were determined. Clinical strains presented a higher prevalence of aggregation substance (agg), enterococcal surface protein (esp) and cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
44
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 41 publications
13
44
3
1
Order By: Relevance
“…The hygienic condition of food handlers is also associated with the propagation of S. aureus biofilm producer (Gutiérrez et al 2012, Souza et al 2014, Di Ciccio et al 2015. Several authors have reported E. faecalis strains isolated from food samples with ability to form biofilms (Medeiros et al 2014, Jahan and Holley 2014, Fernandes et al 2015. Apparently, the biofilm formation by this bacterial species is influenced by several aspects, such as temperature, exposure to nutrients and sanitizers, and surface characteristics (Marinho et al 2013, Fernandes et al 2015.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hygienic condition of food handlers is also associated with the propagation of S. aureus biofilm producer (Gutiérrez et al 2012, Souza et al 2014, Di Ciccio et al 2015. Several authors have reported E. faecalis strains isolated from food samples with ability to form biofilms (Medeiros et al 2014, Jahan and Holley 2014, Fernandes et al 2015. Apparently, the biofilm formation by this bacterial species is influenced by several aspects, such as temperature, exposure to nutrients and sanitizers, and surface characteristics (Marinho et al 2013, Fernandes et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…These strains were genotypically characterized by Medeiros et al (2014) that found the presence of gelatinase (gelE) and cytolysin (cylA) genes. Such virulence factors and phenotypic characteristics of each strain may be associated with metabolic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been more persistently recognized in E. faecalis isolates (9). Medeiros et al (23) reported the invariant incidence of the ace gene among clinical and dairy products of E. faecalis. They have been distinguished the higher fre- Cytolysin operon is carried through plasmid or bacterial chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Medeiros et al, (2014) Lemsaddek et al, 2016), stated that the pathogenesis of foot ulceration is complicated, the death is excessive and ulcers are frequently occurred and lead to severe and chronic infections of the foot. Most DFIs have a poly-microbial etiology, enterococcal strains actuality portion of the multifaceted diabetic foot microbiota.…”
Section: Enterococcus Virulence Genesmentioning
confidence: 99%